Metastatic vulvar Crohn's disease-A rare case report and short review of literature - Debajit Das; Bhaskar Gupta; Mahimanjan Saha (Wolters Kluwer Medknow Publications, 2016)
Metastatic Crohn's disease (CD), a type of extraintestinal CD may present with gynecological manifestation which causes diagnostic dilemma and needs multidisciplinary approach. Vulvar lesions occur in very small number of cases with CD of which asymmetrical labial swelling and edema is the most common presentation. We report a case of hypertrophic exophytic variety of vulvar CD because of its rarity.